2010
DOI: 10.1261/rna.2315010
|View full text |Cite
|
Sign up to set email alerts
|

Four KH domains of the C. elegans Bicaudal-C ortholog GLD-3 form a globular structural platform

Abstract: Caenorhabditis elegans GLD-3 is a five K homology (KH) domain-containing protein involved in the translational control of germline-specific mRNAs during embryogenesis. GLD-3 interacts with the cytoplasmic poly(A)-polymerase GLD-2. The two proteins cooperate to recognize target mRNAs and convert them into a polyadenylated, translationally active state. We report the 2.8-Å -resolution crystal structure of a proteolytically stable fragment encompassing the KH2, KH3, KH4, and KH5 domains of C. elegans GLD-3. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…Hollingworth et al reported that a GDDG double mutation in KH-type splicing regulatory protein (KSRP) impairs nucleic acid binding without compromising KH domain stability (40). The absence or augmentation of the canonical GxxG sequence appears to be a hallmark of impairment of RNA binding (41,42). Our data provide further support for this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…Hollingworth et al reported that a GDDG double mutation in KH-type splicing regulatory protein (KSRP) impairs nucleic acid binding without compromising KH domain stability (40). The absence or augmentation of the canonical GxxG sequence appears to be a hallmark of impairment of RNA binding (41,42). Our data provide further support for this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…Three-dimensional structural analysis has revealed that all fi ve KH domains of GLD-3 have extensive contacts with each other, forming a tightly packaged protein core, which is in contrast to a previously assumed "beads on a string" organization. Consistent with GLD-3 having an extremely low af fi nity for homopolymeric guanidine RNA (Jedamzik and Eckmann, unpublished results), the typical GxxG RNA-contacting loops (G, glycine) of known RNAbinding KH domains are missing either one or both of the two glycine residues (Nakel et al 2010 ) . GLD-3 binds GLD-2, and GLS-1 (see below).…”
Section: Kh Proteinssupporting
confidence: 55%
“…They contain 5 KH domains arranged in tandem connected via very short amino acid linkers, whereby each individual domain adopts a classic KH fold (Eckmann et al 2002 ;Nakel et al 2010 ) . Three-dimensional structural analysis has revealed that all fi ve KH domains of GLD-3 have extensive contacts with each other, forming a tightly packaged protein core, which is in contrast to a previously assumed "beads on a string" organization.…”
Section: Kh Proteinsmentioning
confidence: 99%
“…KH-domains that do not contain the conserved GxxG motif -and do not interact with RNA -can assemble in multi-domain units where more than one KH-KH interface is observed, exemplified by the structure of the type I KH tetra-domain unit of Bicaudal-C (Bic-C) (Figure 4b) [39]. Type II KH domains lacking the GxxG motif have also been recently reported in proteins of the metallo-β-lactamase superfamily.…”
Section: Combinatorial Binding and Architectural Role By Multiple Kh mentioning
confidence: 84%